Cost Service Tradeoffs in Power Utility Procurement - Sutarto, Zulfikar Luthfi; Putera, Rizki Revianto (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Reliable electricity distribution depends on the availability of Main Distribution Materials. Specific Background: Centralized procurement provides cost control but has longer lead time, while decentralized procurement offers faster responses with higher inventory costs. Knowledge Gap: The cost–service trade-off under uncertain demand has not been fully evaluated. Aims: This study compares centralized and decentralized periodic review policies using Monte Carlo simulation based on SAP ERP demand data from 2022–2024 over 300 weeks. Results: Centralized procurement is more cost-efficient in aggregate but has higher stockout risk and lower responsiveness, whereas decentralized procurement improves service level, shortens lead time, and reduces stockout frequency despite higher holding costs. Novelty: The study integrates validated normal demand distribution with Monte Carlo simulation to assess procurement policy performance. Implications: A hybrid policy is recommended, with centralized control for slow-moving materials and decentralized control for critical or fast-moving materials. Highlights: Centralized setting delivers aggregate financial advantage but shows longer lead time and weaker responsiveness. Decentralized setting records stronger service levels, faster response, and fewer shortages. Rising service targets raise safety stock and holding expenses across both settings. Keywords: Supply Chain, Centralized, Decentralized, Main Distribution Materials, Monte Carlo Simulation.